2022
DOI: 10.21203/rs.3.rs-1986918/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of the Duration of Membership in the GATT/WTO on Economic Growth Volatility

Abstract: This article investigates the effect of the duration of membership in the General Agreement on Tariffs and Trade (GATT) and the World Trade Organization (WTO) on economic growth volatility. Using an unbalanced panel dataset of 153 countries over the period 1980-2019, the empirical analysis has revealed that the duration of membership in the GATT/WTO has been associated with lower economic growth volatility, with this negative effect being larger in member states that were subject to rigorous accession procedur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
(87 reference statements)
1
1
0
Order By: Relevance
“…Thus, we postulate that by enhancing export product upgrading, the duration of the membership in the GATT/WTO would reduce economic growth volatility and improve citizens' welfare, in particular their human development level. This line of argument is consistent with the findings by Gnangnon (2022c) that the duration of the membership in the GATT/WTO is associated with lower economic growth volatility in member states. The author has observed that member states that joined the organization under rigorous accession procedures enjoyed a larger negative effect of the membership duration on economic growth volatility than other member states.…”
Section: Introductionsupporting
confidence: 92%
“…Thus, we postulate that by enhancing export product upgrading, the duration of the membership in the GATT/WTO would reduce economic growth volatility and improve citizens' welfare, in particular their human development level. This line of argument is consistent with the findings by Gnangnon (2022c) that the duration of the membership in the GATT/WTO is associated with lower economic growth volatility in member states. The author has observed that member states that joined the organization under rigorous accession procedures enjoyed a larger negative effect of the membership duration on economic growth volatility than other member states.…”
Section: Introductionsupporting
confidence: 92%
“…The choice of control variables in the present analysis is guided by the relatively limited literature on the determinants of welfare (e.g., Bussmann, 2009; Carmignani & Avom, 2010; Gnangnon, 2022; Kosack & Tobin, 2015; Sakyi et al., 2018), as well as the literature on the macroeconomic determinants of ‘development’, the latter being measured from the perspective of economic growth and income inequality (e.g., Carmignani & Chowdhury, 2011) or from the perspective of economic growth, income inequality and poverty (e.g., Santos‐Paulino et al., 2019). The set of control includes the human capital accumulated, the economic growth rate, terms of trade, the inflation rate, the degree of trade openness, the population size, the terms of trade, and the political institutions proxied by the quality of the political system.…”
Section: Empirical Analysismentioning
confidence: 99%